Teachers’ pedagogical improvement who participate in the training and specialization of doctors in Venezuela - Felicia Pérez Moya; Nilzer Agramonte Vargas; Silvia Enríquez Vilaplana; Maribel Torres Cobas (Medisur)
Background: the Comprehensive Community Physician’s Training and Specialization Programs in Venezuela require teachers with a solid pedagogical preparation, capable of organizing and directing the teaching-learning process with quality. Objective: to design teaching tasks that, from the Basic Pedagogy course, favor the didactic-methodological procedure of teachers who participate in the training and specialization of doctors in the context of the Cuban Medical Mission in Venezuela. Methods: a descriptive, pedagogical research was carried out. The theoretical and empirical level methods were applied: analytical-synthetic, inductive-deductive, historical-logical, group interview, participant observation and documentary analysis. The sample was selected intentionally; it was made up of the 35 teachers who participated in the pedagogy courses taught in 2021, in the La Guaira State. Results: study guides were designed with new teaching tasks, structured based on the professional problem, the objective and the subject of study. Evaluative activities were elaborated that favored a better interaction of the teachers with the curricular units of the different academic years and with the students in the assistance scenarios. The teaching tasks had a positive impact on the pedagogical knowledge acquired by the students, verified in the predominance of the medium and high levels of the evaluated dimensions and the observation of an adequate assimilation of the contents, cognitive independence and the application of knowledge to new pedagogical practice situations. Conclusions: the teaching tasks included in the Basic Pedagogy Program contributed to the methodological didactic improvement of teachers.